APLIKASI ETIKA TASAWUF AL-GHAZALI DALAM MEWUJUDKAN GOOD GOVERNANCE DI INDONESIA - Agus Iswanto (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2007)
This article tries to exspose that apllication of tasawuf ethics may be done to actualize Good Governance in Indonesia. The first, I give some argument why I choose tasawuf and Ghazali as a focus in this study. Tasawuf as an Islamic tradition and capacity of Ghazali are two arguments which can be used. Contextualisation of social live of Ghazali can be examined why I choose him. There are three concept from his thought about tasawuf ethic: zuhd, teleologis ethic, and ummahât al-fadhâil. These concepts can be done to practice in reforming Indonesian Good Governance.